The COVID-19 pandemic and eating disorders in children, adolescents, and emerging adults: virtual care recommendations from the Canadian consensus panel during COVID-19 and beyond - Couturier, Jennifer (J Eat Disord, 2021)
OBJECTIVE: The COVID-19 pandemic has had detrimental effects on mental health. Literature on the impact on individuals with eating disorders is slowly emerging. While outpatient eating disorder services in Canada have attempted to transition to virtual care, guidelines related to optimal virtual care in this field are lacking. As such, the objective of our Canadian Consensus Panel was to develop clinical practice guidelines related to the provision of virtual care for children, adolescents, and emerging adults living with an eating disorder, as well as their caregivers, during the COVID-19 pandemic and beyond. METHODS: Using scoping review methodology (with literature in databases from 2000 to 2020 and grey literature from 2010 to 2020), the Grading of Recommendations, Assessment, Development, and Evaluation system, the Appraisal of Guidelines, Research and Evaluation tool, and a panel of diverse stakeholders from across Canada, we developed high quality treatment guidelines that are focused on virtual interventions for children, adolescents, and emerging adults with eating disorders, and their caregivers. RESULTS: Strong recommendations were supported specifically in favour of in-person medical evaluation when necessary for children, adolescents, and emerging adults, and that equity-seeking groups and marginalized youth should be provided equal access to treatment. For children and adolescents, weak recommendations were supported for telehealth family-based treatment (FBT) and online guided parental self-help FBT. For emerging adults, internet cognitive-behavioural therapy (CBT)-based guided self-help was strongly recommended. Weak recommendations for emerging adults included CBT-based group internet interventions as treatment adjuncts, internet-based relapse prevention Maudsley Model of Anorexia Nervosa Treatment for Adults (MANTRA) guided self-help, telehealth relapse prevention using MANTRA, and guided CBT-based smartphone apps as treatment adjuncts. For caregivers of children and adolescents, weak recommendations were supported for virtual parent meal support training, and moderated online caregiver forums and support groups. For caregivers of emerging adults, guided parental self-help CBT was strongly recommended, and unguided caregiver psychoeducation self-help was weakly recommended. CONCLUSIONS: Several gaps for future work were identified including the impact of sex, gender, race, and socioeconomic status on virtual care among children, adolescents, and emerging adults with eating disorders, as well as research on more intensive services, such as virtual day hospitals.